2016
DOI: 10.3390/ijms17071014
|View full text |Cite
|
Sign up to set email alerts
|

Oenocarpus bacaba and Oenocarpus bataua Leaflets and Roots: A New Source of Antioxidant Compounds

Abstract: Native palm trees fruit from the Amazonian rainforest, Oenocarpus bacaba and Oenocarpus bataua, are very often used in the diet of local communities, but the biological activities of their roots and leaflets remain poorly known. Total phenolic content (TPC) and antioxidant activity of root and leaflet extracts from Oenocarpus bacaba and Oenocarpus bataua were assessed by using different chemical assays, the oxygèn radical absorbance capacity (ORAC), the 2,2-diphenyl-l-picrylhydrazyl (DPPH) free radical-scaveng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 61 publications
(78 reference statements)
1
19
0
1
Order By: Relevance
“…The leaf and root extracts contain hydroxycinnamic acids such as caffeoylquinic and caffeoylshikimic acids and C-glycosyl flavones [57]. Stilbene and its derivative, piceatannol, have been isolated from a methanolic extract of the fruit pulp [58].…”
Section: Constituentsmentioning
confidence: 99%
“…The leaf and root extracts contain hydroxycinnamic acids such as caffeoylquinic and caffeoylshikimic acids and C-glycosyl flavones [57]. Stilbene and its derivative, piceatannol, have been isolated from a methanolic extract of the fruit pulp [58].…”
Section: Constituentsmentioning
confidence: 99%
“…oleracea and O . bataua berries [ 14 ], two-fold higher than Oenocarpus leaflets acetone extracts [ 12 ], and slightly lower than green tea (1200 µmol TEq/g DM) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ORAC assay, considered as one of the most relevant amongst antioxidant chemical assays, gave ORAC values from 1600 to 2200 µmol TEq/g DM, for leaflet extracts. They were at least three-fold more active than palm berries in the ORAC assay [ 14 ], at least 1.5-fold more active than the best Oenocarpus leaflet extracts [ 12 ] and almost equivalent to green tea with 2400 µmol TEq/g DM ( Table 1 ). Besides, even if E .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use in folk medicine predicts the functional properties of Bacaba fruits, their nutritional and bioactive potential has not yet been sufficiently studied (Abadio Finco et al, 2016). Several benefits associated with their consumption are reported, such as antioxidant (Leba et al, 2016) and antiproliferative activity (Abadio Finco et al, 2013), and potential chemopreventive activity against carcinogenesis (Abadio Finco et al, 2016). Angelo & Jorge (2007) confirmed that phenolic compounds mainly occur in citrus and tropical fruits, and that they are found in greater quantities in pulp than in fruit juice.…”
Section: Introductionmentioning
confidence: 99%